A male and female gametocyte functional viability assay to identify biologically relevant malaria transmission-blocking drugs. - Ruecker, A; Mathias, D; Straschil, U; Churcher, T; Dinglasan, R; Leroy, D; Sinden, R; Delves, M (American Society for Microbiology, 2014)
Malaria elimination will require interventions that prevent parasite transmission from the human host to the mosquito. Experimentally, this is usually determined by the expensive and laborious Plasmodium falciparum standard membrane feeding assay (PfSMFA), which has limited utility for high-throughput drug screening. In response, we developed the P. falciparum dual gamete formation assay (PfDGFA), which faithfully simulates the initial stages of the PfSMFA in vitro. It utilizes a dual readout that individually and simultaneously reports on the functional viability of male and female mature stage V gametocytes. To validate, we screen the Medicines for Malaria Venture (MMV) Malaria Box library with the PfDGFA. Unique to this assay, we find compounds that target male gametocytes only and also compounds with reversible and irreversible activity. Most importantly, we show that compound activity in the PfDGFA accurately predicts activity in PfSMFAs, which validates and supports its adoption into the transmission-stage screening pipeline.